Keratolysis exfoliativa-like eruption induced by ranolazione - Elena Pierobon; Lerica Germi; Andrea Sechi; Giampaolo Trevisan; Elena Pezzolo; Claudio Feliciani; Luigi Naldi (PAGEPress Publications, 2021)
Dermatoses affecting palms may represent a dermatologic challenge from both the diagnostic, and therapeutic point of view. Patients with supposedly occupational dermatitis can spend months or even years in a frustrating attempt to avoid contact with possible irritants or allergens. To underline the importance of a thorough unbiased analysis of the patient's history and clinical features, we present the iconic case of a bricklayer affected by a chronic, disabling desquamation of palms which in the end was classified as keratolysis exfoliativa (KE) attributed to ranolazine-intake, an antianginal drug. To the best of our knowledge, this specific adverse effect of drug-induced KE of palms has never been reported before in association with ranolazine.